Pelatihan Digitalisasi Pemasaran dan Pencatatan Keuangan di CV. Jaya Utama Konsultan - Izzadieny, Fitra; Rizka, Nor Rahma; Ulfida, Deafatunnizwa; Arini, Rizky Mega; Nurmalina, Radna (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Digital transformation has become a crucial need for businesses, including those in the consulting sector. CV. Jaya Utama Konsultan, a company engaged in architectural and engineering planning based in Banjarbaru, still faces challenges due to its non-digital approach to marketing and financial recording. To address this issue, a team of lecturers from the DIII Accounting Program at Politeknik Negeri Tanah Laut conducted a training program aimed at enhancing the company staff’s digital competencies. The activity was carried out using the Participatory Action Research (PAR) method, which actively involved participants throughout the training process. The training consisted of two main sessions: digital marketing using platforms such as Instagram, WhatsApp Business, and Google My Business, and financial recording using Excel and digital applications like Zahir. The sessions were conducted interactively and received enthusiastic responses from 20 participants. Based on pre- and post-training questionnaires, there was a significant improvement in participants’ understanding and skills. Around 90% of participants were able to operate basic digital media for promotion and perform structured financial recording efficiently. This training not only supports operational efficiency and transparency but is also expected to serve as a model for other small businesses in Banjarbaru in adapting to the digital era.